Pengaruh pertumbuhan ekonomi, upah minimum dan jumlah tenaga kerja terhadap kemiskinan di Kota Jambi Tahun 2000 – 2017 - Fahrur Rozi; Yulmardi Yulmardi; Etik Umiyati (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2019)
This study aims to: 1) Know and analyze the development of economic growth, minimum wages, number of workers and poverty levels in Jambi City; and 2) To find out and analyze the influence of economic growth, minimum wages and the number of workers and poverty levels in Jambi City. The analytical tool used in this study is multiple linear regression.The results of this study are that economic growth in Jambi City experienced fluctuations during 2000-2017. The minimum wage in the city of Jambi has increased annually during 2000-2017. Labor in Jambi City experienced fluctuations during 2000-2017. The poverty rate in Jambi City experienced annual fluctuations during 2000-2017. From the results of the processed multiple linear regression that the variable economic growth, minimum wage, labor simultaneously have a significant effect on the level of poverty, it can be seen from the significant value of 0.002 which is smaller than 0.05. While partially the independent variables that influence the poverty level are minimum wages and labor, it can be seen from the significant values ​​smaller than 0.05. Keywords: Economic Growth, Minimum Wage, Number of Labor, and Poverty Levels.